Advantageous effects of rumen-protected phytonutrients from tropical plant extracts on rumen fermentation efficiency and methane mitigation using in vitro fermentation technique - Maharach Matra; Chaichana Suriyapha; Gamonmas Dagaew; Rittikeard Prachumchai; Srisan Phupaboon; Sukruthai Sommai; Metha Wanapat (Animal Bioscience)
Objective Tropical plants are composed of phytonutrients (PTNs) and are utilized for their capacity to manipulate rumen fermentation characteristics and methane production. The aim of this experiment was to determine the impact of microencapsulated PTNs-extracted from lemongrass and mangosteen peel (M-LEMANGOS), as well as crude protein (CP) levels on nutrient degradability, rumen ecology, microbial population, and methane emission in an in vitro study. Methods The treatments were randomly assigned in a 2×4 Factorial arrangement in a completely randomized design. The two factors consisted of CP percentage in the concentrate diet (16% and 18% CP) and the levels of M-LEMANGOS addition (0%, 2%, 4%, and 6% of the total substrate). Results The results showed that nutrient degradability both 12 and 24 h were significantly increased with M-LEMANGOS at 4% total substate. In part of volatile fatty acids (VFAs), particularly propionate and total VFA, these were enhanced by %CP and M-LEMANGOS combination. The %CP increased ruminal ammonia-nitrogen concentration (NH3-N), while M-LEMANGOS supplementation reduced such concentration. Methane production and Methanobacteriales population at 12 and 24 h were reduced when supplemented with M-LEMANGOS at 4% total substate. The population of Fibrobacter succinogenes, Ruminococcus flavefaciens, and Megasphaera elsdenii were increased with the interaction between %CP and M-LEMANGOS addition. Conclusion M-LEMANGOS indicates promising potential as a plant-based PTN for dietary modulation of rumen fermentation and mitigation of methane production.